Pengaruh Strategi Orientasi Wirausaha dan Orientasi Pasar Pengaruhnya Terhadap Kinerja Perusahaan UMKM di Kota Surabaya - Sumiati Sumiati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2015)
Abstract: The aims of this study to analyze the influence of Entrepreneur orientation and market orientation to corporate performance of Small Medium Scale Industries (SMEs) in Surabaya. This study include descriptive exploratory methodes with taking 75 sample of SMEs with the owner or manager as respondents, data gathered by using questionnaire instrument. The results showed that the effect of variable- entrepreneurial oriented is significantly influence to corporate performance, but the marketing orientation dit not significantly affect to corporate performance of SMEs in the city of Surabaya, while the hypothesis test using F-test shows that there is significantly influence between Entrepreneur and Market oriented to corporate performance because the value of probability significant found smaller than alfa 0.05, this mean that the SMEs in Surabaya should adopt Entreprenuer oriented for continue the operation of their business. Besides, SMEs also should adopt market oriented to improve performance and highly competitive, especially in the face of the implementation of the Asean Economic Community in the end of 2015.Key words: Entreprenuer Oriented, Market Oriented and SMEs performance.